Alteration of serum thymus and activation‐regulated chemokine level during biologic therapy for psoriasis: Possibility as a marker reflecting favorable response to anti‐interleukin‐17A agents. Issue 6 (14th April 2018) - Shibuya, Takashi; Honma, Masaru; Iinuma, Shin; Iwasaki, Takeshi; Takahashi, Hidetoshi; Ishida‐Yamamoto, Akemi
Abstract: Biologics show great efficacy in treating psoriasis, a chronic inflammatory skin disease. The high cost and side‐effects of biologics, dose‐reduction, elongation of administration interval and suspension are possible options. However, there has been no reliable biomarker we can use when we consider these moderations in therapy. This study was conducted to test the possibility of using serum thymus and activation‐regulated chemokine (TARC) level as an indicator for step down of biologic therapy. Serum TARC level was measured in 70 psoriatic patients at Asahikawa Medical University, and a correlation of TARC and severity of skin lesions was analyzed. Referring to serum TARC level, psoriatic patients can be divided into two groups. One is a population in which serum TARC level is positively correlated with severity of skin lesions, and the other is a population with low psoriatic severity and high TARC level. Serum TARC level was higher in the group that achieved PASI‐clear with biologics than in the group which did not achieve PASI‐clear. Among biologics, the group treated with secukinumab, an anti‐interleukin (IL)‐17A agent, showed significantly higher TARC level compared with the group treated with anti‐tumor necrosis factor agents. In certain populations achieving PASI‐clear, serum TARC level may be a potent marker reflecting better response to IL‐17A inhibitors, and in this case step down of treatment for psoriasis is possible.